The Pyramids of Egyt - O'Donnell, Kerri; Nang Chan Yeema (New York, United State The Rosen Publishing Group, Inc., 2003)
Explores the history of Egypt's Pyramids, including a brief look at how they were constructed, who was buried in them, and the religious significance of the structures and their contents
Keywords: Juvenile Nonfiction